Evaluation of rainbow trout (Oncorhynchus mykiss) organotypic intestinal platforms: cellular responses after long-term exposure to in vitro digested feed - Verdile, Nicole; Camin, Federica; Chacon, Marcelo A.; Pasquariello, Rolando; Pavlovic, Radmila; Peggs, David; Fontanillas, Ramon; Tandler, Amos; Kortner, Trond M.; Bitan, Amir; Brevini, Tiziana A. L.; Gandolfi, Fulvio (Frontiers in Marine Science, 2023)
Reliable and predictive in vitro models would support the search for new raw materials that can improve current fish diets. We recently developed some rainbow trout (RT) intestinal cell-based organotypic platforms demonstrating that the platform type modulates the degree of cell differentiation achieved in vitro and here we studied whether such differentiation correlates with their response to a prolonged exposure to a diet rich in fish meal. We compared three options, seeding the RTpiMI and RTdiMI cell lines derived respectively from the proximal or the distal intestine on (1) the polyethylene terephthalate (PET) culture inserts ThinCert™ (TC); (2) the TC coated with RT fibroblasts embedded within Matrigel® (MMfb); and (3) the highly porous polystyrene scaffold Alvetex™ also populated with fibroblasts (AV). Platforms have been exposed for 21 days to increasing concentrations of feed pellets digested in vitro by gastric and intestinal RT enzymes (IVD). Cells exposed to culture medium without IVD in each platform were used as controls. TEER values became significantly higher than their respective controls in most culture conditions. At the end of culture, epithelial cells formed multilayers irrespective of cell line or platforms if exposed to IVD, but not in the controls. This proliferative activity followed a dose-dependent pattern in the AV, did not vary in MMfb, and was highly variable in the TC. Moreover, IVD induced the formation of a few goblet-like cells characterized by rounded vacuoles. In parallel, alanine aminopeptidase activity completely disappeared in the MMfb, significantly decreased in the AV, but did not change in TC. These changes suggest a de-differentiation of the enterocytes and their partial differentiation towards the secretory lineages. Overall, the three platforms reacted differently to a pronged exposure to IVD: TC quenched most of the cell responses, MMfb generated overly sensitive reactions, while the AV react mostly in a dose-dependent manner possibly generating more physiological results.